The social transmission of spatial information in homing pigeons. - Burt de perera T; Guilford, T (1999)
We adapted a technique to explore the social transmission of spatial information in homing pigeons Columba livia. Five demonstrator pigeons were first trained to find a food goal within an indoor arena. This arena consisted of nine lidded cups laid out within a 12x12 grid on the floor. The task was to find the goal cup and flip the lid to obtain the food hidden within. Once the demonstrators had reached criterion the experiment proper began. During stage 1 of the experiment, 10 target birds, which had not previously been trained to find the goal, were introduced to the spatial task either in isolation or paired with a demonstrator. We measured how long they took to complete the task, the number of squares crossed on the grid, and the number of incorrect lids flipped. In stage 2, the target birds were introduced to the arena a second time, by themselves, and we compared the performance of the birds in the two treatments. The pigeons that had been introduced to the task with a demonstrator in stage 1 walked further and made more incorrect choices when searching for the food goal in stage 2 than the pigeons that were introduced to the task alone. This indicates that pigeons learn a spatial, food-finding task more effectively when performing the task alone than when accompanied by a knowledgeable conspecific. We discuss possible reasons for this in the light of previous experiments. Copyright 1999 The Association for the Study of Animal Behaviour.